Target Sales and Profit Analysis through the Approach Break Even Point (BEP) at PT. Hotel Sahid International Tbk. - Sri Sutrismi; Nurani Nurani; Miratul Zahiroh (Institute of Computer Science (IOCS), 2022)
This research has the objectives of: (1) Want to know the increase in process costs and cost sales grace period 2016-2019. (2) Want to know the size of the sales target when the break-even point or reach the Break Even Point. (3) Want to know the impact of changes in one of the factors causing changes in profit to changes in the company's break-even point (BEP). The data collection method used in this study is documentation The data analysis method used in this research is Breakeven point analysis by adding up fixed costs and variable costs or total costs deducted from sales, it will be able to know where the break-even point or the company's position when it does not experience profit or not suffer losses. Based on the results of the study it is known that in order for companies to seek achieve the profit target and the sales gain as expected, one of the ways that is carried out is by optimizing the marketing cost by ten percent (10%), then the impact is not only on the break-even point but also the profit achievement can be IDR. 3,331,204,860.